Numerical Simulation of 980 nm-LD-Pumped Yb3+-Er3+-Tm3+-Codoped Fiber Amplifier for 1500 nm and 1600 nm Bands. (11th June 2009) - Jiang, Chun
Abstract : The theoretical model ofYb 3 + -Er 3 + -Tm 3 + -codoped fiber amplifier pumped by 980 nm laser is proposed, and the rate and power propagation equations are numerically solved to analyze the dependences of the gains at 1500 nm and 1600 nm bands on the activator concentrations, fiber length, pump power, and signal wavelength. The numerical results show that our model is in good agreement with experimental result, and with pump power of 200 mW and fiber length varying from 0.15 to 1.5 m, the gains at the two bands may reach 10.0–20.0 dB when the codoping concentrations ofYb 3 +, Er 3 +, andTm 3 + are in the ranges 1.0–3.0 × 10 25, 1.0–3.0 × 10 24, and 1.0–3.0 × 10 24 ions/m 3, respectively. The fiber parameters may be optimized to flatten the gain spectra.